Effectiveness of Financial Management at the Department of Finance and Revenue Management Regional Property Tomohon. - Nangka, Nadia Gabriela; Mandey, Jantje; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT   Reform of financial management can’t be separated from the purpose regional autonomy  itself, which  in addition to  improving public services, both qualitatively and  quantitatively, also  in order to  allocate resources  efficiently  and  effectively, as well as the  achievement of the space  for  public participation  in developing  regions. The principles  of financial management, namely  accountability,  honesty  in  managing  finances,  transparent,  and  responsible  in  observing  the  principle of fairness, compliance, and benefits to society.   Needed  a  system  that  could  provide  reasonable  assurance  that  the  implementation  of  the  activities  at  a  Government  Agency  can  achieve  the  objectives  efficiently  and  effectively,  financial  management  report  are  reliable,  secure  state  assets,  and  encourage  adherence  to  regulations.  This  system  is known  as the  internal control system  in its application should take fairness  and  compliance  as  well  as  considering  the  size,  complexity  and  nature  of  the  tasks  and  functions  of  the  Government  Agencies.  Internal  control  in  government  is  considered  very  necessary  to  avoid  actions  that  might  be  cheating   or   have   been   made   by   the   various   parties   engaged   in   the   world   of   government.   In  implementing  these  internal  control,  related  parties  refers  to  government  regulation  No.  60  of  2008.  However, in reality this control is not maximized applied in government activities.   Results     of   research   conducted        through   the   collection   of       data   obtained     through  observation,  documents  and  interviews.  The  results  showed  that  the  financial  management  process  almost  goes  well,  because  there  are  things  that  may  impede  the  process  of  managing  their own  will. But  thanks to  a sense of  teamwork  that is  high  on  every  employees  in  service  income of the financial and property management areas in Tomohon, can make the work good.   Runway  and  references  used  in  the  process  of  financial  management  in  the  life  of  the  Financial Management and Revenue office property in the area Tomohon Pemendagri No.  13 of  2006.   Keywords: Fiscal Management